Chemokine Therapy in Cats With Experimental Renal Fibrosis and in a Kidney Disease Pilot Study - Bennington, Julie; Lankford, Shannon; Magalhaes, Renata S.; Shankle, Douglas; Fanning, Jason; Kartini, Cucu; Suparto, Irma; Kusumawardhani, Winda; Putra, M. ArRaniri; Mariya, Silmi; Badlani, Gopal; Williams, J. Koudy (Frontiers in Veterinary Science, 2021)
Background. Chronic tubulointerstitial fibrosis is a common final pathway leading to end stage kidney disease in cats and has no effective treatment. The use of cell-based molecules to treat kidney fibrosis may be a promising approach. The objectives were to test the effects of intra-renal chemokine CXCL12 injection in a preclinical cat model of unilateral ischemia/reperfusion (I/R)-induced kidney fibrosis and then, within a clinical pilot study, test the safety/feasibility of CXCL12 injection in cats that might have early chronic kidney disease (CKD). Methods: Preclinical: Thirty cats received intra-renal injection of 100, 200, or 400ng of recombinant human CXCL12, or sterile saline, into the I/R kidney 70 days post-injury, or were non-injured, non-injected controls (n=6/group). Kidney collagen content was quantified 4 months post-treatment using Masson’s Trichrome and Picrosirius Red (PSR) stained tissues. In a separate study (n=2) exploring short-term effects of CXCL12, 200ng CXCL12 was injected into I/R kidneys and then harvested either 30 minutes (n=1) or 1 month (n=1) post-injection. Kidney concentrations of CXCL12, matrix metalloproteinase 1 (MMP-1), and lysyl oxidase-like enzyme 2 (LOXL-2) were quantified via ELISA. Clinical Pilot: 14 client-owned cats with potential early kidney disease received a single-treatment, bilateral intra-renal injection of 200ng CXCL12 (n=7), or received no injection (n=7). Blood/urine samples were collected monthly for 9 months to assess renal function and CKD staging. Results: Preclinical: I/R increased the affected kidney collagen content, which both mid and high doses of CXCL12 restored to normal (ps<.05 vs. untreated). I/R increased collagen fiber width, which both mid and high doses of CXCL12 restored to normal (p<.001 vs. untreated). Early changes in kidney MMP-1, associated with collagen breakdown, and subsequent decreases in LOXL-2, associated with collagen cross-linking, in response to CXCL12 treatment may contribute to these findings. Clinical Pilot: Bilateral intra-renal injection of CXCL12 using ultrasound guidance in cats with CKD was feasible and safe in a general practice clinical setting with no obvious side effects noted during the 9-month follow-up period. Conclusions: Intra-renal injection of CXCL12 may prove to be an effective treatment for kidney fibrosis in cats with CKD. Additional mechanistic and clinical evaluations are needed.